Investigating the Internship Experiences and Adaptation Strategies of International Students - Wu, Tzu-Ying; Tsai, Chin-Fa; Leelapattana, Winitra; Thongma , Weerapon (Journal of Ecohumanism, 2025)
In the contemporary global educational landscape, the internship experiences of international students constitute a critical area of investigation, particularly considering how such experiences contribute to the development of effective adaptation strategies in unfamiliar cultural and professional milieus. This study employs a mixed-methods approach, integrating both qualitative and quantitative data, to examine the internship engagements of international students and the resultant adaptive measures they undertake. By surveying a representative sample of 150 international students who have completed internships in diverse industry sectors, and conducting in-depth interviews with 30 participants, the research illuminates the varying challenges and learning opportunities encountered by these students. The analysis is grounded in the framework of experiential learning and cultural adjustment theories, offering a holistic view of the internships’ impact on students’ professional and personal growth. We articulate the patterns of adaptation that emerge, ranging from the acquisition of industry-specific knowledge to the enhancement of cross-cultural competencies. The findings contribute to a nuanced understanding of international students’ experiential learning cycle during internships and provide actionable insights for educators, policymakers, and businesses to optimize support mechanisms for this demography. The conclusion emphasizes the importance of aligning educational programs with practical experiences to foster global-ready professionals.